1964
DOI: 10.1161/01.cir.29.6.825
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and Cardiovascular Function in Patients with Severe Pulmonary Hypertension

Abstract: applied the term hypertensive pulmonary vascular disease to patients with chronic, severe pulmonary hypertension. They emphasized that this disease is a distinct clinicopathologic entity with uniform clinical features and characteristic morphologic changes of the pulmonary arteries and arterioles irrespective of the etiology of the hypertension. The vascular changes indicate restriction of the pulmonary vascular bed, which may alter pulmonary gas exchange. This study of the respiratory physiology of such patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

1965
1965
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 15 publications
1
13
0
1
Order By: Relevance
“…The combination of alveolar hyperventilation and increased (parallel) dead space ventilation is remarkable as it puts an extra ventilatory drive on an already increased effort of breathing. These findings are in unison with reports in patients with iPAH (Meyer et al, 2005;Wessel et al, 1964;Zoia et al, 2002). The alveolar hyperventilation seemed to be only in part hypoxic driven, as administration of 100% oxygen for at least 20 minutes increased but did not normalize Pa,CO 2 (4.50 ± 0.42 kPa vs. 4.58 ± 0.42 kPa).…”
Section: Pathophysiology Of Dyspnea In Ctephsupporting
confidence: 84%
See 1 more Smart Citation
“…The combination of alveolar hyperventilation and increased (parallel) dead space ventilation is remarkable as it puts an extra ventilatory drive on an already increased effort of breathing. These findings are in unison with reports in patients with iPAH (Meyer et al, 2005;Wessel et al, 1964;Zoia et al, 2002). The alveolar hyperventilation seemed to be only in part hypoxic driven, as administration of 100% oxygen for at least 20 minutes increased but did not normalize Pa,CO 2 (4.50 ± 0.42 kPa vs. 4.58 ± 0.42 kPa).…”
Section: Pathophysiology Of Dyspnea In Ctephsupporting
confidence: 84%
“…In the past, abnormalities in coagulation and fibrinolysis pathways have been identified in CTEPH patients, however, the frequency of these defects in such patients were similar to those in the general population. Lupus anticoagulant and antiphospholipid antibodies were shown to be present in 10-20% of patients with CTEPH, which is higher than in patients with acute venous thromboembolism (Auger et al, 1995;Wolf et al, 2000). Bonderman et al showed increased levels of factor VIII (FVIII) in about 40% of CTEPH patients as compared to both healthy controls and patients with non-thromboembolic pulmonary hypertension (Bonderman et al, 2003).…”
Section: Pathophysiology Of Ctephmentioning
confidence: 99%
“…The picture is further complicated, especially in mitral valve disease, by the oc currence of obliterative lesions involving in itially the small peripheral branches of the pulmonary arterial tree. This is accompa nied by thrombosis, thromboembolism and functional vascoconstriction [Parker and Weiss, 1936;Wessel et al, 1964;Forster, 1957;Hamer, 1965;Aber and Campbell, 1965;Yu, 1969], giving rise to an inflow obstruction of the alveolar capillary system. This results in a decrease of Vcv.…”
Section: Discussionmentioning
confidence: 99%
“…T h erefo re, th e m e c h a n ic al fu n c tio n o f lu n g s a n d th o ra x is re la tiv e ly u n d is tu rb e d a n d sig n ifican t changes in th is re g a rd do n o t o ccu r u n til th e o n set o f h e a r t failu re. A slight in crease o f resid u al v o lu m e a n d R V /T L C ra tio in o u r a n d a few o th e r p a tie n ts [23,26] is m ore likely re la te d to c o m p lic a tin g o b stru c tiv e a irw a y disease and th is is n o t a com m on finding [19,24], T h e re m a rk a b le e x te rn a l h y p e rv e n tila tio n e x h ib ite d b y o u r p a tie n t has been n o te d b y o th e rs [24,26]. I t re su lts in in creased w ork of b re a th in g w hich larg ely a c c o u n ts fo r th e co m p lain t of d y sp n e a .…”
Section: R Espiratory Pathophysiologymentioning
confidence: 99%
“…T h e diffusing c a p a c ity is u su a lly n o rm al or slig h tly red u ced [22,23,31] a n d th is w as so in o u r case. A ny re d u c tio n m u st b e th e resu lt o f a d ecrease in th e effective area of th e m e m b ra n e r a th e r th a n an in crease in its thickness.…”
Section: R Espiratory Pathophysiologymentioning
confidence: 99%